Trapped-wave modes of bodies in channels. (22nd December 2016) - Newman, J. N.
Abstract : Trapped waves can exist in the presence of bodies in open water, and also in channels of finite width. Various examples are found for bodies that support trapped waves in channels, including floating and submerged bodies and bottom-mounted cylinders. Different types of trapping are considered where the body is fixed or free to move in response to the oscillatory pressure. In some cases both types are supported by the same body. In most cases for fixed bodies the fluid motion is antisymmetric about the centreline of the channel, but special body shapes exist where the trapped mode is asymmetric. For free bodies the trapping modes and body motions are symmetric about the centreline if the body is floating or antisymmetric if it is submerged.